Denying a patient's final will: Public safety vs. medical confidentiality and patient autonomy - Gaertner, Jan; Vent, Julia; Greinwald, Ralf; Rothschild, Markus A.; Ostgathe, Christoph; Kessel, Rene; Voltz, Raymond (Journal of Pain and Symptom Management, 2011)
Especially when caring for patients approaching the end of life, physicians and nursing staff feel committed to fulfilling as many patient desires as possible. However, sometimes a patient's "final will" may threaten public safety. This can lead to severe conflicts, outweighing the physician's obligation and dedication to care for the patient and to respect his autonomy. Yet, public safety can be threatened if confidentiality is not broken. This article provides a concise summary of the medicolegal and ethical fundamentals concerning this difficult situation. If the patient's and others' health and safety are at risk, physicians may (and in some countries must) break medical confidentiality and disclose confidential patient information to the police and other authorities. Physicians should be able to professionally deal with such a conflict in all patients, not only in patients with advanced illness. © 2011 U.S. Cancer Pain Relief Committee Published by Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2025-10-27
Keywords: automobile driving; confidentiality; conflict of interest; ethics; forensic medicine; Palliative care; personal autonomy; safety management